The association between dietary vitamins and the risk of sarcopenia in adults aged 20–59: a study based on the NHANES database - Qiu, Yu; Zhao, Fengyi; Zheng, Xiyin; Wang, Xiaohua (Frontiers in Nutrition, 2025)
BackgroundSarcopenia has emerged as a global health concern, but the association between dietary vitamin levels and sarcopenia is not elucidated. This study aims to shed light on the link of 11 dietary vitamins to the risk of sarcopenia in adults at the age of 20–59.MethodsThis cross-sectional study encompassed 2011–2018 data from the National Health and Nutrition Examination Survey (NHANES) for adults aged 20–59. Sarcopenia was defined through the appendicular lean mass to body mass index ratio calculated via Dual-Energy X-ray Absorptiometry (DXA), with sarcopenia determined as a ratio of <0.789 for the male and <0.512 for the female. Multivariate weighted logistic regression assisted in assessing the connection of dietary vitamins with sarcopenia, with results presented as odds ratios (ORs) and 95% confidence intervals (CIs). The dose-response association of various vitamins with sarcopenia was visualized through restricted cubic splines (RCS). Subgroup analyses were carried out to examine the consistency of the aforementioned associations. Sensitivity analysis was performed utilizing propensity score matching (PSM) to adjust for confounding factors and enhance the robustness of the results.ResultsAmong the 7,864 participants, 677 (8.6%) had sarcopenia, and 7,187 (91.4%) did not. Multivariate weighted logistic regression and RCS analyses indicated that higher intakes of VA, VB1, VB2, VB3, VB6, VB9, VB12, VC, VE, and VK were notably linked to a lowered risk of sarcopenia (P < 0.05). Among these, VA, VC, and VE exhibited a non-linear negative association with sarcopenia risk (P for non-linear < 0.05), while VB1, VB2, VB3, VB6, VB9, VB12, and VK exhibited a linear negative association (P for non-linear > 0.05). Subgroup analysis yielded largely consistent results. After confounding factors were adjusted through PSM, the results suggest that the intake of VA, VB2, VB6, and VC remains significantly associated with a lowered risk of sarcopenia (P < 0.05).ConclusionHigher dietary levels of VA, VB2, VB6, and VC are significantly related to a lower livelihood of sarcopenia. These findings provide new evidence and insights for early dietary interventions aimed at preventing sarcopenia.